The Impact of Workforce Diversity and Organizational Culture on Employee Retention in EJIP Manufacturing Companies - Yuniastri, Salsabila Dwi; Karyati, Siti (Lentera Ilmu Nusantara, 2025)
This study examines the influence of workforce diversity and organizational culture on employee retention in manufacturing companies in EJIP industrial estates. In an increasingly competitive global era, employee retention is crucial for organizational stability and performance. High turnover rates lead to increased operational costs, decreased productivity, and loss of organizational knowledge. The diversity of the workforce, which includes characteristics such as gender, age, ethnicity, and educational background, has the potential to increase creativity and innovation but also poses challenges in human resource management. Meanwhile, organizational culture greatly influences employee behavior and engagement, especially in creating an inclusive and supportive work environment. This study uses a quantitative approach, with data from 75 manufacturing employees collected through purposive sampling techniques. The results of the study show a positive and significant influence of workforce diversity and organizational culture on employee retention. The study emphasizes the importance of effective diversity management and the development of inclusive organizational practices to improve employee retention, reduce turnover, and improve performance in the manufacturing sector.